2002
DOI: 10.1038/sj.onc.1205131
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of Cyr61 in human breast cancer cell lines

Abstract: We have shown that Cyr61, an angiogenic regulator, is overexpressed in invasive and metastatic human breast cancer cells and tumor biopsies. We have further demonstrated that Cyr61 promotes acquisition of estrogen-independence and anti-estrogen resistance in vivo in breast cancer cells. Moreover, we have demonstrated that Cyr61 induces tumor formation and tumor vascularization in vivo, events mediated through the activation of the MAPK and the Akt signaling pathways. Here we investigate how Cyr61 expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Expression of cyr61 has been reported to be induced by estrogen in breast cancer cells [69,70] and human myometrial explants [70], which is consistent with the up-regulation of cyr61 expression in our study. Expression of bcl2 was down-regulated in our study, but previous reports have shown both induction and repression of bcl-2 expression by estrogen, potentially in a tissue specific manner [71-75].…”
Section: Discussionsupporting
confidence: 92%
“…Expression of cyr61 has been reported to be induced by estrogen in breast cancer cells [69,70] and human myometrial explants [70], which is consistent with the up-regulation of cyr61 expression in our study. Expression of bcl2 was down-regulated in our study, but previous reports have shown both induction and repression of bcl-2 expression by estrogen, potentially in a tissue specific manner [71-75].…”
Section: Discussionsupporting
confidence: 92%
“…A higher level of Cyr61 is found in breast cancer and it is shown to induce estrogen-independence and to promote invasiveness of breast cancer [32]. Cyr61 is shown to have elevated mRNA and protein levels in pancreatic cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of CYR61 mRNA is rapidly induced in an immediate early response manner by a spectrum of stimuli including growth factors, cytokines and estrogens [58-60]. We have demonstrated cyclical regulation of CYR61 in baboon endometrium, with maximal mRNA levels observed in shed menstrual endometrium [56].…”
Section: Angiogenic Profile Of Endometriotic Tissuesmentioning
confidence: 99%